Factors influencing stabilometry parameters of the individual standing on the different orthopedic insole - O. V. Kubryak; V. I. Nechyaev (Спортивная медицина: наука и практика, 2020)
Objective: the analysis of changes in stabilometric indices during the successive standing of the test subject on various types of orthopedic insoles, focusing on the study of the influencing factors. Materials and methods: 38 healthy volunteers (26 women and 12 men), aged 37±5 with out pathology of feet, experimental insoles of different hardness, stabilometry, mathematical analysis. Results: the effect of the «novelty» of the material affects the stability of the vertical posture. Conclusions: among other possible factors, when designing an adequate technique for analyzing the effectiveness of foot orthotics, it is necessary to take into account the full range of possible non-target influencing factors, including fast ones, such as the «novelty» factor.